Lithium ion sieve and preparation method thereof
By covering the gel isolation layer on the surface of the lithium ion sieve precursor and performing acid activation treatment, the lack of liquidity, filtration and permeability of the lithium ion sieve powdered materials is solved, and its adsorption effect and industrial application potential are improved.
Patent Information
- Application Number
- CN202411877815.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium ion sieves are mostly powdery, resulting in poor performance in fluidity, filtration and permeability, limiting their application and development on industrial scale.
By covering the gel isolation layer on the surface of the lithium ion sieve precursor and using an acid solution to perform acid activation in subsequent steps, the gel isolation layer is removed, and the exposed area and adsorption effect of the lithium ion sieve are improved.
It improves the adsorption effect of lithium ion sieve, enhances its application potential in industrial production, and solves the shortcomings of powdered materials in terms of fluidity, filtration and permeability.
Smart Images

Figure CN119657066A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion sieves, in particular to a lithium ion sieve and a preparation method thereof. Background Art
[0002] As the lightest metal element, lithium is regarded as an important strategic resource due to its strong electrochemical activity. It is widely used in many fields, including lithium-ion batteries, thermonuclear fusion reactors, aerospace technology, glass and ceramic manufacturing, etc. With the continuous expansion of these applications, the demand for lithium has also shown an increasing trend year by year. At present, the supply of lithium resources mainly depends on lithium ore and liquid lithium resources (such as salt lake brine). However, with the gradual reduction of lithium ore resources, lithium resources in salt lake brine have become more and more important, and its reserves account for 59% of the world's total lithium resources. In particular, my country has rich salt lake brine lithium resources, and its lithium content accounts for about 85% of the country's total lithium resources. Therefore, extracting lithium from salt lake brine has become the mainstream direction of current and future lithium resource development. In the process of extracting lithium from salt lake brine, adsorption is a commonly used method, and its core lies in the use of efficient adsorbents. Lithium ion sieve is a class of inorganic adsorbents with excellent performance, which can capture lithium ions from liquid lithium resources with high selectivity. Li2TiO3, Li4Ti5O 12 Materials such as LiMn2O4 are widely used as materials for lithium ion sieves due to their excellent lithium ion selectivity. This type of material not only has a strong theoretical absorption capacity, but also has low raw material regeneration loss, relatively low energy consumption, and an environmentally friendly lithium extraction process. Despite these significant advantages, the lithium ion sieves currently synthesized are mostly powdery substances, which results in their poor performance in terms of fluidity, filterability and permeability, thus limiting their application and development on an industrial scale. In order to overcome these problems, granulation of lithium ion sieves is a feasible solution that can significantly improve their physical properties and promote their widespread application in industrial production.
[0003] The Chinese patent application with publication number CN 118142487 A mixes an adsorbent precursor, an adhesive forming agent, a pore-forming agent and a forming aid, and heats the resulting mixture under high pressure, kneads, heats and extrudes, cools and shapes, cuts, acid-activates, and dries to obtain a lithium ion sieve adsorbent. Although this method adds a pore-forming agent, the overall processability deteriorates with the increase of inorganic components, and the resin ratio needs to be increased to adjust the flow properties of the melt. However, the increase in resin will also cause the adsorbent powder to be wrapped and the exposure area to be low. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a lithium ion sieve and a preparation method thereof in view of the deficiencies in the prior art, thereby increasing the exposure area of the adsorbent in the lithium ion sieve and improving the adsorption effect of the lithium ion sieve.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A preparation method of a lithium ion sieve comprises mixing a lithium ion sieve precursor, an adhesive forming agent and a pore-forming agent, and heating and extruding the obtained mixture to obtain particles A; mixing the particles A with an acid solution, performing acid activation, and drying to obtain a lithium ion sieve adsorbent; the surface of the lithium ion sieve precursor is coated with a gel isolation layer, and the gel isolation layer can react with acid.
[0007] Principle: A gel isolation layer is evenly coated on the surface of lithium ion sieve precursor particles.
[0008] Advantages: A gel isolation layer is coated on the surface of the lithium ion sieve precursor in advance. The gel isolation layer can be dissolved and removed after soaking in acid in the subsequent steps to reduce the wrapping area of the adhesive forming agent on the surface of the lithium ion sieve during granulation and increase the contact area between the lithium ion sieve precursor and brine.
[0009] In a preferred embodiment of the present invention, the gel isolation layer is one or more of a magnesium hydroxide gel isolation layer, an aluminum hydroxide gel isolation layer, a ferric hydroxide gel isolation layer, a ferrous hydroxide gel isolation layer, and a zinc hydroxide gel isolation layer; preferably, the gel isolation layer is a magnesium hydroxide gel isolation layer.
[0010] In a preferred embodiment of the present invention, the preparation method of the gel isolation layer coated on the surface of the lithium ion sieve precursor comprises slurrying the lithium ion sieve precursor powder with water, adding a dispersant for grinding and dispersing, adding a soluble metal salt solution, dripping an alkaline solution, aging, filtering, washing, drying, and then crushing; the metal salt solution is a magnesium salt solution, and the alkaline solution is a sodium hydroxide solution.
[0011] In a preferred embodiment of the present invention, the magnesium salt solution is a soluble magnesium salt including one or more of magnesium sulfate, magnesium citrate, magnesium nitrate, and magnesium chloride, the concentration of the magnesium salt solution is 5-20wt%, and the amount of the magnesium salt solution added is 1-10% of the weight of the lithium ion sieve precursor, calculated as MgO; the concentration of the sodium hydroxide solution is 10-40wt%; preferably, the concentration of the magnesium salt solution is 5-10wt%, and the amount of the magnesium salt solution added is 5-10% of the weight of the lithium ion sieve precursor, calculated as MgO; the concentration of the sodium hydroxide solution is 30-40wt%. This concentration range can ensure higher production capacity.
[0012] In a preferred embodiment of the present invention, the sodium hydroxide solution is added for 0.5 to 1 hour, and the final pH value is adjusted to ≥ 7.0; preferably, the sodium hydroxide solution is added for 0.5 to 1 hour, and the final pH value is adjusted to 7.0 to 9.0. When the pH is less than 7, the magnesium hydroxide precipitation is incomplete, and when the pH is greater than 9, the alkali is wasted and the residual alkali is not easy to wash away.
[0013] In a preferred embodiment of the present invention, the adhesive forming agent is one or more of PVC, CPVC, and PVDC. Preferably, the adhesive forming agent is PVC. Before the particles A are mixed with the acid solution, an alkaline solution soaking step is also included: the particles A are soaked, heated, and washed with water using an alkaline solution.
[0014] Principle: This step is hydrophilic modification. PVC will undergo a dechlorination reaction in a hot alkaline solution, which can increase the hydroxyl groups on the surface of PVC and make the resin more hydrophilic.
[0015] Advantages: Compared with grafting reaction, the use of PVC dechlorination to increase hydroxyl groups in situ makes the reaction conditions easier to control, the cost is lower, and no other impurities are introduced.
[0016] The gel isolation layer can protect the lithium ion sieve precursor from being corroded by the alkali solution and having its structure destroyed during the alkali solution heat treatment in step 4.
[0017] In a preferred embodiment of the present invention, in the alkaline solution soaking step, 1-5wt% of an oxidant is added to the alkaline solution, and the oxidant includes one or more of hydrogen peroxide and sodium hypochlorite; preferably, 1-3wt% of an oxidant is added to the alkaline solution. Too high an oxidant will cause excessive oxidation of PVC, resulting in a decrease in material strength; too low an oxidant will not be enough, the oxidation of PVC is not strong, the hydroxyl content is low, and good hydrophilicity cannot be achieved.
[0018] Adding an oxidant can promote the reaction and partially degrade PVC, increasing the surface hydroxyl groups.
[0019] In a preferred embodiment of the present invention, the concentration of the alkali solution in the alkali solution soaking step is in the range of 10-40wt%, and the heating temperature is 90-110°C; preferably, the concentration of the alkali solution in the alkali solution soaking step is in the range of 30-40wt%, and the heating temperature is 95-105°C. The higher the temperature and alkali solution concentration, the stronger the ability to replace chlorine in PVC. In addition, a higher sodium hydroxide concentration can increase the boiling point of water and achieve a higher temperature treatment. 95°C is the lower limit for a sufficient reaction amount to occur, and 105°C is the upper limit of the boiling point.
[0020] The present invention includes the following specific contents:
[0021] (1) The lithium ion sieve precursor powder is slurried with water, a dispersant is added for grinding and dispersion, a magnesium salt solution is added, a sodium hydroxide solution is added dropwise to adjust the pH, the mixture is aged for 1 hour, filtered, washed with water, dried, and crushed again to obtain powder A.
[0022] Specific parameter range: wherein the lithium ion sieve precursor comprises Li2TiO3, Li4Ti5O 12 , LiMn2O4, etc., the beating concentration is 100-300g / L; the dispersant can be one or more of polycarboxylate, sodium hexametaphosphate, sodium pyrophosphate, sodium silicate, sodium dodecylbenzene sulfonate; the grinding method can be one of sand milling, ball milling, high-stirring dispersion, colloid milling, and ultrasonic dispersion; the magnesium salt is a soluble magnesium salt containing one or more of magnesium sulfate, magnesium citrate, magnesium nitrate, and magnesium chloride, with a mass concentration of 5-20%, and the addition amount is 1-10% of the weight of the lithium ion sieve (in terms of MgO); the concentration of the sodium hydroxide solution is 10-40%, the dripping time is controlled at 0.5-1h, and the final pH value is adjusted to ≥7.0. The drying temperature is 60-130°C, and the re-crushing method is air flow crushing.
[0023] (2) The powder A is mixed evenly with PVC, a plasticizer and a pore-forming agent, extruded by a twin-screw extruder, cooled in cold water and pelletized to obtain pellets A.
[0024] Specific parameter range: powder A accounts for 40-90% of the total component mass; the PVC powder accounts for 10-30% of the total component mass; the plasticizer comprises one or more combinations of epoxidized soybean oil, epoxy methyl ester, DOP, DOTP, DMAC, and DMF, accounting for 10-30% of the total component mass; the pore-forming agent comprises one or more combinations of Mg(OH)2, MgO, PEG, glycerol, glucose, and sucrose, and the added amount is 5-20% of the PVC mass; the screw length of the screw extruder is ≥50cm, the temperature is controlled at 120-170°C, the cold water temperature is ≤10°C, and the particle size is controlled at a diameter of 0.5-2mm and a length of 3-8mm.
[0025] Principle: After powder A is mixed with PVC, plasticizer and pore-forming agent in a twin-screw extruder, PVC and plasticizer swell and melt, wrapping the other materials mentioned above to form a melt. After being extruded through the die, it drips into water and cools into lines, and is cut into particles by a cutting machine. Among them, PVC plays the role of bonding and fixing the lithium ion sieve, the plasticizer is used to increase the fluidity of the components, reduce the melting point of PVC, and can reduce the amount of PVC and increase the exposure area of the ion sieve. The pore-forming agent can be removed during water immersion or acid immersion, leaving gaps and increasing the channels in the PVC layer. The screw length is to ensure uniform mixing, and the cold water temperature is to ensure that the melt has sufficient hardness for cutting.
[0026] Advantages: Simple process, low cost, ordinary plastic extrusion pelletizing equipment can meet the production needs. The particle size is controllable, the particle strength is high, and the porosity is high.
[0027] (3) removing the plasticizer from the particles by solvent soaking and extraction, and drying to remove the solvent to obtain particles B;
[0028] Specific parameter range: The solvent selection range is that the solvent cannot dissolve PVC but can dissolve the extraction plasticizer, including but not limited to: one or more of ethyl acetate, methanol, ethanol, and tetrabutyl acetate. The solvent immersion extraction time is 2 to 3 hours.
[0029] Principle: After the plasticizer is extracted and removed, the volume of PVC shrinks, leaving some pores in the original particles.
[0030] Advantages: Plasticizers and solvents can be recycled and reused. The porosity of particles prepared by this method is higher than that of particles prepared without using plasticizers.
[0031] (4) using an alkaline solution to heat-immerse the particles B, and washing with water to obtain particles C;
[0032] Specific parameter range: the alkali solution contains sodium hydroxide, lithium hydroxide and potassium hydroxide solution; the concentration range is 10-40wt%, the heat treatment temperature is 90-110°C, the heat soaking time is 2-3h, and 1-5wt% of an oxidant is added to the alkali solution, including hydrogen peroxide or sodium hypochlorite.
[0033] (5) The particles C are soaked in acid to transform the particles and obtain lithium ion sieve particles.
[0034] Specific parameters: Acid concentration 0.05-1 mol / L, acid includes one or more of hydrochloric acid, sulfuric acid, nitric acid, citric acid, oxalic acid, acetic acid. Soaking temperature 20-60℃, acid to particle ratio 10:1, acid is replaced every 5 hours, a total of more than 4 times, washed with pure water.
[0035] Principle: Use acid soaking process for H + The acid can exchange ions with the Li in the lithium ion sieve precursor to convert it into an H-type lithium ion sieve. At the same time, the acid can soak and dissolve the pore-forming agent and the magnesium hydroxide gel coated on the surface of the lithium ion sieve.
[0036] Advantages: The acid leaching transformation step is used to simultaneously remove the pore former and the magnesium hydroxide coating layer. The process is simple and the porosity can be improved without adding processing steps.
[0037] The invention also discloses a lithium ion sieve prepared by using the preparation method of the lithium ion sieve.
[0038] The present invention also discloses a lithium ion sieve, wherein the contact angle between the lithium ion sieve and water is 40-55°, the Li removal rate of the lithium ion sieve is ≥99%, and the operable adsorption capacity of the lithium ion sieve is 13-17 mg / g; preferably, the contact angle between the lithium ion sieve and water is 40-52°, the Li removal rate of the lithium ion sieve is ≥99.5%, and the operable adsorption capacity of the lithium ion sieve is 13-16.5 mg / g.
[0039] The Chinese patent with publication number CN 118142487 A also has the problem that most resins will affect the wetting of water in the pores without hydrophilic modification, thereby affecting the mass transfer of lithium ions. The present application utilizes hydrophilic modification, and PVC will undergo a dechlorination reaction in a hot alkaline solution, which can increase the hydroxyl groups on the surface of PVC and make the resin more hydrophilic.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) Pre-coating the lithium ion sieve powder with magnesium oxide or the like to produce a gel isolation layer to prevent resin wrapping, which is removed during acid leaching to increase the contact area between the powder and the brine and improve the adsorption efficiency.
[0042] (2) Using Cl on the PVC surface - The groups are easily replaced by OH- groups under strong alkaline conditions, thereby improving the hydrophilicity of the material.
[0043] (3) Use plasticizers to increase the volume of the organic phase after compatibility with the resin, improve the processing performance of the melt without increasing the amount of resin, and leave pores after solvent extraction to improve the adsorption efficiency.
[0044] (4) Add water-soluble / acid-fusible pore-forming agents, which can be removed during the acid leaching step to increase the porosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a photograph of the contact angle between the sample prepared in Example 1 of the present invention and water.
[0046] Figure 2 This is a photograph of the contact angle between the sample prepared in Example 2 of the present invention and water.
[0047] Figure 3 This is a photograph of the contact angle between the sample prepared in Example 3 of the present invention and water.
[0048] Figure 4 This is a photograph of the contact angle between the sample prepared in Comparative Example 1 of the present invention and water.
[0049] Figure 5 This is a photograph of the contact angle between the sample prepared in Comparative Example 2 of the present invention and water. DETAILED DESCRIPTION
[0050] Embodiment 1:
[0051] S1 Mix 250g of Li2TiO3 powder with water to control the concentration to 250g / L, add 1g of sodium polycarboxylate, and sand grind for 1h. After grinding, the slurry is heated to 40°C, 10% magnesium sulfate solution is added according to the mass of MgO = 12.5g, 40% sodium hydroxide solution is added dropwise to adjust the pH to 9.0, the dropping time is 1h, mature for 1h, filter, wash with water, dry at 80°C, and crush to obtain powder A.
[0052] S2 is prepared by mixing 200 g of powder A, 60 g of PVC, 60 g of DOP and 80 g of MgO in a mass ratio and extruding into a cylindrical shape using a twin-screw extruder. The screw length of the screw extruder is ≥ 50 cm, the temperature is controlled at 120°C, the cold water temperature is 10°C, and the pellets are cooled and granulated in cold water to form pellets A with a diameter of 0.8 to 1 mm and a length of 3 to 6 mm.
[0053] S3: Using ethyl acetate to soak the particles A for 2 hours to remove the plasticizer in the particles, and drying to remove the solvent to obtain particles B;
[0054] S4: adding 1% sodium hypochlorite to 1000g 30% sodium hydroxide solution to soak particle B, controlling the temperature at 95°C for 2h, and washing with water to obtain particle C;
[0055] S5: Take 50g of the above particles C and soak them in 1L 1mol / L citric acid solution at 40°C. Replace the acid solution every 5h. Repeat 5 times. After washing with pure water, the transformation is completed to obtain lithium ion sieve particles.
[0056] Example 2
[0057] S1 Mix 250g of LiMn2O4 powder with water to control the concentration to 250g / L, add 1g of sodium polycarboxylate, and sand grind for 1h. After grinding, the slurry is heated to 40°C, 10% magnesium sulfate solution is added according to the mass of MgO = 12.5g, 40% sodium hydroxide solution is added dropwise to adjust the pH to 9.0, the dropping time is 1h, mature for 1h, filter, wash with water, dry at 80°C, and crush to obtain powder A.
[0058] S2 is prepared by mixing 200 g of powder A, 60 g of PVC, 60 g of DOP and 80 g of MgO in a mass ratio and extruding into a cylindrical shape using a twin-screw extruder. The screw length of the screw extruder is ≥ 50 cm, the temperature is controlled at 120°C, the cold water temperature is 10°C, and the pellets are cooled and granulated in cold water to form pellets A with a diameter of 0.8 to 1 mm and a length of 3 to 6 mm.
[0059] S3: Using ethyl acetate to soak the particles A for 2 hours to remove the plasticizer in the particles, and drying to remove the solvent to obtain particles B;
[0060] S4: adding 1% sodium hypochlorite to 1000g 30% sodium hydroxide solution to soak particle B, controlling the temperature at 95°C for 2h, and washing with water to obtain particle C;
[0061] S5: Take 50g of the above particles C and soak them in 1L 0.5mol / L citric acid solution at 40°C. Replace the acid solution every 5h. Repeat 5 times. After washing with pure water, the transformation is completed to obtain lithium ion sieve particles.
[0062] Example 3
[0063] S1 Mix 250g of Li2TiO3 powder with water to control the concentration to 250g / L, add 0.5g of sodium hexametaphosphate, and sand grind for 1h. After grinding, the slurry is heated to 60℃, 10% magnesium chloride solution is added according to the mass of MgO = 25g, 30% sodium hydroxide solution is added dropwise to adjust the pH to 8.5, the dropping time is 1h, mature for 1h, filter, wash with water, dry at 80℃, and crush to obtain powder A.
[0064] S2 is prepared according to the following mass ratio: a mixture of 200 g of powder A, 50 g of PVC, 50 g of DOP and 60 g of Mg(OH)2. The mixture is extruded into a cylindrical shape using a twin-screw extruder. The screw length of the screw extruder is ≥ 50 cm. The temperature is controlled at 120°C, the cold water temperature is 10°C, and the mixture is cooled and pelletized in cold water to produce particles A with a diameter of 0.8 to 1 mm and a length of 3 to 6 mm.
[0065] S3: soaking and extracting particles A in ethyl acetate for 3 hours to remove the plasticizer in the particles, and drying to remove the solvent to obtain particles B;
[0066] S4: adding 1% hydrogen peroxide to 1000g 40% sodium hydroxide solution to soak particle B, controlling the temperature at 103°C, soaking time for 2h, and washing with water to obtain particle C;
[0067] S5: Take 50g of the above particles C and soak them in 1L 1mol / L citric acid solution at 40°C. Replace the acid solution every 5h. Repeat 5 times. After washing with pure water, the transformation is completed to obtain lithium ion sieve particles.
[0068] Comparative Example 1 (Preparation method in prior art)
[0069] S1 is prepared by mixing 200 g of Li2TiO3 powder, 120 g of PVC and 80 g of MgO in a mass ratio, extruded into a cylindrical shape using a twin-screw extruder, cooled and pelletized in cold water to form particles A with a diameter of 0.8 to 1 mm and a length of 3 to 6 mm.
[0070] S2: Take 50g of the above particles A and soak them in 1L 1mol / L citric acid solution at 40°C. Replace the acid solution every 5h. Repeat 5 times. After washing with pure water, the transformation is completed to obtain lithium ion sieve particles.
[0071] Comparative Example 2 (the difference from Example 1 is that the S4 step in Example 1 is not included)
[0072] S1 Mix 250g of Li2TiO3 powder with water to control the concentration to 250g / L, add 1g of sodium polycarboxylate, and sand grind for 1h. After grinding, the slurry is heated to 40°C, 10% magnesium sulfate solution is added according to the mass of MgO = 12.5g, 40% sodium hydroxide solution is added dropwise to adjust the pH to 9.0, mature for 1h, filter, wash with water, dry at 80°C, and crush to obtain powder A.
[0073] S2 is prepared by mixing 200 g of powder A, 60 g of PVC, 60 g of DOP and 80 g of MgO in a mass ratio, extruded into a cylindrical shape using a twin-screw extruder, cooled and pelletized in cold water to produce particles A with a diameter of 0.8 to 1 mm and a length of 3 to 6 mm.
[0074] S3: soaking and extracting particles A in ethyl acetate for 2 hours to remove the plasticizer in the particles, and drying to remove the solvent to obtain particles B;
[0075] S4: Take 50g of the above particles B and soak them in 1L 1mol / L citric acid solution at 40°C. Replace the acid solution every 5h. Repeat 5 times. After washing with pure water, the transformation is completed to obtain lithium ion sieve particles.
[0076] The contact angle with water and the operable adsorption capacity of the samples of the above-mentioned Examples 1 to 3 and Comparative Examples 1 and 2 were tested. The test method of the operable adsorption capacity is as follows:
[0077] Preparation of simulated brine: Weigh the following reagents separately: 1.60 g lithium carbonate, 7.61 g sodium bicarbonate, 10.58 g anhydrous sodium sulfate, 11.86 g anhydrous sodium carbonate, 78.31 g sodium chloride, dissolve them and adjust the volume to 1 L.
[0078] Test method: accurately weigh 1.00±0.05g of activated lithium ion sieve adsorbent particles, put them into a 200ml plastic bottle, add 100mL of the above-prepared brine, put them into a water bath shaker, set the water bath temperature to 25°C, rotate at 150-180rpm / min, shake for 4h, take water samples to detect the lithium ion concentration in the solution before and after adsorption (detected by ICP-OES inductively coupled plasma emission spectroscopy), and calculate the operational lithium adsorption capacity of the material. The formula is as follows:
[0079]
[0080] Among them, C0 (mg / L) is the initial lithium ion concentration of the adsorption solution; Ct (mg / L) is the lithium ion concentration of the solution after 4 hours of adsorption; m (g) is the mass of the lithium ion sieve particles; Qt (mg / g) is the operable exchange capacity of the material.
[0081] The test results are shown in Table 1.
[0082] Table 1 Test results of Examples 1-3 and Comparative Examples 1-2
[0083]
[0084]
Claims
1. A method for preparing a lithium ion sieve, comprising mixing a lithium ion sieve precursor, a bonding agent, and a pore-forming agent, and heating and extruding the resulting mixture to obtain particles A; mixing the particles A with an acid solution, performing acid activation, and drying to obtain a lithium ion sieve adsorbent; characterized in that: The surface of the lithium ion sieve precursor is coated with a gel isolation layer, and the gel isolation layer can react with acid.
2. The method for preparing a lithium ion sieve according to claim 1, characterized in that: The gel isolation layer is one or more of a magnesium hydroxide gel isolation layer, an aluminum hydroxide gel isolation layer, a ferric hydroxide gel isolation layer, a ferrous hydroxide gel isolation layer, and a zinc hydroxide gel isolation layer; preferably, the gel isolation layer is a magnesium hydroxide gel isolation layer.
3. The method for preparing a lithium ion sieve according to claim 1, characterized in that: The preparation method of the gel isolation layer coated on the surface of the lithium ion sieve precursor comprises slurrying the lithium ion sieve precursor powder with water, adding a dispersant for grinding and dispersion, adding a soluble metal salt solution, dropping an alkali solution, aging, filtering, washing, drying, and then pulverizing; The metal salt solution is a magnesium salt solution, and the alkali solution is a sodium hydroxide solution.
4. The method for preparing a lithium ion sieve according to claim 3, characterized in that: The magnesium salt solution is a soluble magnesium salt, including one or more of magnesium sulfate, magnesium citrate, magnesium nitrate, and magnesium chloride. The concentration of the magnesium salt solution is 5-20wt%, and the amount of the magnesium salt solution added is 1-10% of the weight of the lithium ion sieve precursor, calculated as MgO; the concentration of the sodium hydroxide solution is 10-40wt%; preferably, the concentration of the magnesium salt solution is 5-10wt%, and the amount of the magnesium salt solution added is 5-10% of the weight of the lithium ion sieve precursor, calculated as MgO; the concentration of the sodium hydroxide solution is 30-40wt%.
5. The method for preparing a lithium ion sieve according to claim 4, characterized in that: The sodium hydroxide solution is added dropwise for 0.5 to 1 h, and the final pH value is adjusted to be ≥ 7.0; preferably, the sodium hydroxide solution is added dropwise for 0.7 to 1 h, and the final pH value is adjusted to be 7.0 to 9.
0.
6. The method for preparing a lithium ion sieve according to any one of claims 1 to 5, characterized in that: The adhesive forming agent is one or more of PVC, CPVC, and PVDC. Preferably, the adhesive forming agent is PVC. Before the particles A are mixed with the acid solution, an alkali solution soaking step is also included: the particles A are soaked, heated, and washed with water using the alkali solution.
7. The method for preparing a lithium ion sieve according to claim 6, characterized in that: In the alkaline solution soaking step, 1 to 5 wt% of an oxidant is added to the alkaline solution, and the oxidant includes one or more of hydrogen peroxide and sodium hypochlorite; preferably, 1 to 3 wt% of an oxidant is added to the alkaline solution.
8. The method for preparing a lithium ion sieve according to claim 6, characterized in that: The concentration of the alkali solution in the alkali solution soaking step is in the range of 10-40wt%, and the heating temperature is 90-110°C; preferably, the concentration of the alkali solution in the alkali solution soaking step is in the range of 30-40wt%, and the heating temperature is 95-105°C.
9. A lithium ion sieve prepared by the method for preparing a lithium ion sieve according to any one of claims 1 to 8.
10. A lithium ion sieve, characterized in that: The contact angle between the lithium ion sieve and water is 40-55°, the Li removal rate of the lithium ion sieve is ≥99%, and the operable adsorption capacity of the lithium ion sieve is 13-17 mg / g; preferably, the contact angle between the lithium ion sieve and water is 40-52°, the Li removal rate of the lithium ion sieve is ≥99.5%, and the operable adsorption capacity of the lithium ion sieve is 13-16.5 mg / g.
Citation Information
Patent Citations
Method for preparing lithium ion sieve adsorbent based on thermal forming
CN118142487A